2000
DOI: 10.1001/jama.283.20.2661
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Maternal Mortality in Japan

Abstract: Inadequate obstetric services are associated with maternal mortality in Japan. Reducing single-obstetrician only delivery patterns and establishing regional 24-hour inpatient obstetrics facilities for high-risk cases may reduce maternal mortality in Japan. JAMA. 2000;283:2661-2667.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 9 publications
3
48
0
1
Order By: Relevance
“…The results of the study corresponds to those of the studies conducted by Montazeri et al (2008) in Kermanshah and Najaya et al (2000) in Japan [18] [19]. In the present study, concerning the hospital where delivery is done, X 2 test showed that there is a significant difference between the two groups, control and subject group.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study corresponds to those of the studies conducted by Montazeri et al (2008) in Kermanshah and Najaya et al (2000) in Japan [18] [19]. In the present study, concerning the hospital where delivery is done, X 2 test showed that there is a significant difference between the two groups, control and subject group.…”
Section: Discussionsupporting
confidence: 90%
“…It occurs in about 2.5% of pregnant Japanese women (1) and results in substantial maternal and neonatal morbidity and mortality (2,3). Although some types of gene polymorphisms are associated with the occurrence of preeclampsia (4)(5)(6), the pathophysiology of preeclampsia remains uncertain despite significant research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia (pregnancy induced hypertension with proteinuria) is associated with maternal and infantile morbidity and mortality (1,2). The Japan Society for the Study of Hypertension in Pregnancy (JSSHP) classifies preeclampsia into early and late onset type according to whether the clinical manifestations occur before or after 32 weeks of gestation, respectively (3).…”
Section: Introductionmentioning
confidence: 99%